SEEKING WHAT IS PURE, DOING WHAT IS TRUE, AND LIVING A LIFE OF LOVE: Pastoral Leadership and Self-Sacrifice in the Gospel of John - Nguyen, Peter; Romero, M. (Science et Esprit, 2022)
Through an examination of five central passages in the Gospel of John and a consideration of significant religious symbols in this Gospel, we offer a theological reading to show that Christian leaders, who contemplate the Crucified Christ as the pledge of God’s devotion to humankind, are profoundly converted at the interior level. Because of their unrestricted availability to be a shepherd to others, a Christian leader, saved by the love of the Father in Jesus, comes to recognize with gratitude that it is this self-sacrificial love that makes him become a gift to others and that by accepting it, a reciprocal devotion to others ensues. We conclude that the Fourth Gospel demonstrates that ecclesial leadership is founded on Christ’s love and, if it is accepted as such, is not an organizational necessity but an act of service.